Cycle time reduction in deck roller assembly production unit with value stream mapping analysis - Gangala, Chaitanya (2017)
Cycle time reduction is of paramount importance in a manufacturing industry as the customer not only emphasizes on the quality of the product but also takes into consideration the timely delivery of the product. The proposed framework and the advanced methodology in this paper are capable of dealing with each stage of the considered manufacturing unit by maximizing the value of the product through reduction of cycle times and minimization of waste. The time required for all the processes in the manufacturing of the deck rollers is identified and are classified into value added (VA) and non-value added (NVA). Finally, the cycle times were reduced by applying the lean tools and principles on some managerial relevances. Also, Arena software was used to simulate the current and future value stream maps and the change in the cycle times, waiting times, machine utilization, etc. was determined.